Implementasi Desentralisasi Pendidikan di SMA Negeri 6 Batang Hari - Sari, Dina Ratna; Trisoni, Ridwal (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2023)
Education decentralization brings positive and negative impacts for every school that implements it. The purpose of this study was to determine the implementation of education decentralization in SMA Negeri 6 Batang Hari. The type of this research is descriptive qualitative research. Respondents in this study were 5 people, namely the principal, vice principals, teachers and education staff. The instrument of this research is an interview guide on the implementation of education decentralization in SMA negeri 6 Batang Hari. The data collection technique in this research is through structured and depth interviews. The data analysis technique used in this study is the SWOT technique (Strengths, Weaknesses, Opportunity, Threats). The results of this study indicate that: 1) the form of education decentralization in SMA Negeri 6 Batang Hari is School-based Management (SBM), school zoning systems, and the integration of technology in educational activities, 2) the positive impact of education decentralization in SMA Negeri 6 Batang Hari is an increasing quality of education, efficiency of education administration and education equalization, 3) the negative impact of education decentralization in SMA Negeri 6 Batang Hari, namely the presence of new incompetent powers, the existence of gaps for the practice of Corruption, Collusion and Nepotism, and poses other challenges